PENGARUH KONTRASEPSI HORMONAL PIL TERHADAP PERUBAHAN BERAT BADAN IBU MENYUSUI POSTPARTUM - , AGUS TRI RATMOKO, Prof. dr. Siswanto Agus Wilopo, SU., MSc., ScD. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: To improve of contraceptive use, the program of Family Planning and Reproductive Health oriented on the fulfillment of the demand quality services including the use of contraception and protection against the side effects that could be caused. The use of the pill in Yogyakarta had considerable percentage of 36,4%, so it is necessary protection against the side effects thereof. Objective: To determine the differences in weight change of maternal postpartum breastfeeding who use hormonal and non-hormonal contraception. Method: The study was mix randomized clinical trial the samples were breastfeeding mothers since 4 weeks post-delivery who visited the clinic and want to use the contraceptive, with a total sample of 107 respondents. They would be followed up to 6 months and evaluated each month. Analysis of the data used was to see the giving pills patterns containing Lynestrenol and Levonorgestrel with the characteristics of the respondents. Bivariate data analysis used statistical test chi square and one way Anova with 95 % Confidence Interval (p < 0,05). Multivariate data analysis used linear regression statistical test. Results: The users of levonorgestrel had a value of regression coefficient of - 0,44